Empowering smart city governance through decentralized blockchain solutions for security and privacy in IoT communications - Zainuddin, Ahmad Anwar; Muhammad, Nurul Fadhilah Ahmad; Hasli, Amir Husaini Mohd; Zaini, Nor Ani Jannah Ahmad; Karimudin, Nureen Batrisyia Balqis; Bahri, Hannah Sabrina Saiful; Nizam, Muhamad Khaleesh Mirza Khairul; Kamarudin, Saidatul Izyanie; Ghazalli, Nasyitah (Bulletin of Social Informatics Theory and Application, 2023)
This paper highlights the benefits and challenges of smart cities, which leverage technology to offer a wide range of services to citizens. While these services have the potential to greatly improve the quality of life in metropolitan areas, they also raise significant privacy and security concerns. The study emphasizes the need to employ "privacy by design" principles to ensure that personal data is protected throughout the entire lifecycle of data, and data owners have the self-control to manage their data according to their preferences. Smart contracts, built on blockchain technology, offer a secure and transparent way of conducting transactions, particularly in e-governance, and automating processes. By leveraging these technologies, smart cities can address the privacy and security challenges they face while continuing to offer cutting-edge services to their inhabitants. Ultimately, the study emphasizes the importance of a proactive approach to privacy and security in the development and implementation of smart cities.